Study of Multiple Stenosed Artery with Periodic Body Acceleration in Presence of Magnetic Field - and Selvaraj K., Elangovan K. (International Journal of Scientific Research and Management (IJSRM), 2016)
The purpose of this paper is to study the characteristics of blood flow through the multi stenosed artery under the influence of periodic body acceleration in the presence of magnetic field. A math- ematical model has been developed by considering blood as an incompressible Casson fluid and the small blood vessel as a circular tube. The non-linear equations governing the flow are solved and the effects of magnetic field, the body acceleration of blood on velocity, the volumetric flow rate in stenotic region and the wall shear stress on the surface of stenosis are obtained by applying perturbation method. The results are discussed in detail with the help of graphs for the variation of different flow parameters. Some obtained results of blood flow through a multi stenosed artery are of appreciable importance in Medical Science.